Discontent and its civilizations : dispatches from Lahore, New York, and London - Hamid, Mohsin, 1971- (New York : Riverhead Books, 2014)
"From the bestselling author of How to Get Filthy Rich in Rising Asia, an intimate and sharply observed commentary-in-essays on life, art, politics, and "the war on terror.""--
Keywords: Literary criticism -- Books & Reading